Adenosine reduces sinoatrial node cell action potential firing rate by uncoupling its membrane and calcium clocks - Wirth, Ashley N.; Tsutsui, Kenta; Maltsev, Victor A.; Lakatta, Edward G. (Frontiers in Physiology, 2022)
The spontaneous action potential (AP) firing rate of sinoatrial nodal cells (SANC) is regulated by a system of intracellular Ca2+ and membrane ion current clocks driven by Ca2+-calmodulin-activated adenylyl cyclase-protein kinase-A signaling. The mean AP-cycle length (APCL) and APCL variability inform on the effectiveness of clock coupling. Endogenous ATP metabolite adenosine binds to adenosine receptors (A1, A3) that couple to Gi protein-coupled receptors, reducing spontaneous AP firing rate via Gβγ signaling that activates IKAdo. Adenosine also inhibits adenylyl cyclase activity via Gαi signaling, impacting cAMP-mediated protein kinase-A-dependent protein phosphorylation. We hypothesize that in addition to IKAdo activation, adenosine impacts also Ca2+ via Gαi signaling and that both effects reduce AP firing rate by reducing the effectiveness of the Ca2+ and membrane clock coupling. To this end, we measured Ca2+ and membrane potential characteristics in enzymatically isolated single rabbit SANC. 10 µM adenosine substantially increased both the mean APCL (on average by 43%, n=10) and AP beat-to-beat variability from 5.1±1.7% to 7.2±2.0% (n=10) measured via membrane potential and 5.0±2.2 to 10.6±5.9 (n=40) measured via Ca2+ (assessed as the coefficient of variability =SD/mean). These effects were mediated by hyperpolarization of the maximum diastolic membrane potential (membrane clock effect) and suppression of diastolic local Ca2+releases (LCRs) (Ca2+-clock effect): as LCR size distributions shifted to smaller values, the time of LCR occurrence during diastolic depolarization (LCR period) became prolonged, and the ensemble LCR signal became reduced. The tight linear relationship of coupling between LCR period to the APCL in the presence of adenosine “drifted” upward and leftward, i.e. for a given LCR period, APCL was prolonged, becoming non-linear indicating clock uncoupling. An extreme case of uncoupling occurred at higher adenosine concentrations (>100 µM): small stochastic LCRs failed to self-organize and synchronize to the membrane clock, thus creating a failed attempt to generate an AP resulting in arrhythmia and cessation of AP firing. Thus, the effects of adenosine to activate Gβγ and IKACh,Ado and to activate Gαi, suppressing adenylyl cyclase activity, both contribute to the adenosine-induced increase in the mean APCL and APCL variability by reducing the fidelity of clock coupling and AP firing rate.